Perilaku Pembunuhan Berencana Ditinjau dari Pendekatan Behavioristik - Liviani Suryanata; Yusti Probowati Rahayu (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
This study aims to find out how the premeditated murder behavior are occured. The study aims to reveal how participants lived in childhood, experiences in teenagers, and the lives of participant after became an army soldier. The research used qualitative approach with life history method. Data collected using structured interview method consisting of 1 core participant. The result of data analysis shows that during his childhood, participant did not have an emotional attachment with his parents. In adolesence, participant was involved in a peer group who brings him to substance abuse and manipulative behavior. As an army soldier, participant observed a model of violence which aggravates his way to criminal behavior. This lifepath is conditioning for participant to use violence as a way to reach his goals.